Diseño y análisis de una lente metálica dual-band usando la teoría de modos característicos para aplicaciones en banda K/Ka. - Poaquiza Masaquiza, Bryan Fernando (2023)
At present, the development of technology in the field of telecommunications is growing significantly. The increase in the demand for data traffic, satellite communications, new applications, and new devices related to the Internet of Things (IoT) and communication systems based on 5G networks requires the use of new frequencies of the radio spectrum, particularly in the range of the millimeter waves, because of the greater bandwidth available and less interference. Therefore, lenses are an essential element in solving the challenges of today's devices since they provide great directivity and low losses, which are the primary conditions antennas must satisfy for new communication systems. This project aims to design and analyze a metallic lens through the Theory of Characteristic Modes capable of operating in the K and Ka bands. The proposed antenna has been simulated using the CST Studio Suite simulator software; the antenna operates in the double band at a resonant frequency of 20 GHz and 30 GHz simultaneously, and the metallic structure has been optimized in shape and size based on previous studies of lens antennas. In addition, lens feeders developed with a low level of cross-polarization are studied to operate in microwave and millimeter-wave frequencies. For the analysis through the Theory of Characteristic Modes and to describe the modal behavior and provide a physical vision of the radiation characteristics of the metallic structure in a defined frequency range, Altair FEKO is used, thus obtaining the modal significance parameters, characteristic angle, and the contribution of each mode to the total radiated power when a plane wave impinges on a conducting body. This document consists of 5 chapters. The first chapter outlines the approach to the problem and the objectives. In the second chapter, a study is carried out using the Theory of Characteristic Modes in the design of lenses. Then, in the third chapter, the antenna design proposal is presented, consisting of 3-layer metal rings fed by a square opening with two slots. Subsequently, the main simulated results of the structure proposed in the fourth chapter are presented. Y finally, in the fifth chapter, the conclusions of the research project are established. Keywords: Characteristic modes, millimetric waves, antenna design, double band.